EVALUATION OF PENILE MORPHOLOGY SATISFACTION AND SEXUAL FUNCTION IN ADULT MALES FOLLOWING HYPOSPADIAS REPAIR USING TRANSVERSE PEDICLED PREPUTIAL FLAP (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the long-term outcomes regarding urinary and sexual functions, cosmetic perception, and reproductive psychology in adult males undergoing surgical correction for hypospadias using the transverse pedicled preputial island flap technique.Subjects and methods: A cross-sectional descriptive study was conducted on 18 adult patients with a history of hypospadias who underwent urethral reconstruction using a transverse preputial flap. Assessment tools included the penile perception score (PPS) and the international index of erectile function (IIEF-5).Results: The overall satisfaction rate regarding penile morphology reached 88.8% (including 66.6% satisfied and 22.2% very satisfied); only 11.2% expressed dissatisfaction due to retracting scar tissue or residual curvature. The vast majority of patients exhibited normal erectile function, with only 1 case (5.6%) presenting with moderate erectile dysfunction.Conclusion: Urethroplasty using a transverse preputial flap yields favorable and stable long-term outcomes in both urinary and sexual functions for most patients. The comprehensive success of the surgery should be evaluated based on both anatomical restoration and the patient-reported quality of life. Future studies with larger sample sizes and longer follow-up periods are required for the most objective assessment.
Keywords: Hypospadias, penile perception, sexual health, erectile dysfunction.